PERPUSTAKAAN DI ERA DIGITAL : ANTARA REALITA DAN IDEALITAS (STUDI KASUS PERPUSTAKAAN SEKOLAH MENENGAH ATAS DI KABUPATEN SUMENEP) - Syaifuddin, Mufti; Mas’odi, Mas’odi (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2021)
The school library, which should continue to develop in order to improve services to students or school residents, raises a reality that is not as it should be. There is still a library that operates as it is, far from being worthy of being the heart of a school. There needs to be improvement and development as an effort to create a generation who likes reading. The school library in the high school environment (SMA) is still inadequate if it is seen as a proper school library. The difference in viewpoints regarding libraries for policy makers at the internal level becomes an obstacle in realizing school libraries in developing better libraries. The purpose of this research is to try to see the reality and ideals that take place in the process of library management at the high school level in Sumenep district. The method used in this study includes the use of a qualitative approach used to see a series of conditions in the school library at the high school level and the equivalent. The available sampling method was chosen by the researcher to facilitate the retrieval of information in this study. This method provides space for informants and researchers to create openness and availability of research subjects in the process of extracting more in-depth information. It can be concluded from the results of this study that the implementation of policies that have different perspectives on libraries for policy makers at the internal level is an obstacle in realizing school libraries in developing better libraries. There are also school library staff who show that it is not proportional to the number of study groups in a school.